2014
DOI: 10.1021/jo502004r
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Dimers of 1,3-Diphenylisobenzofuran for Singlet Fission: Synthesis and Electrochemistry

Abstract: The synthesis of covalent dimers in which two 1,3-diphenylisobenzofuran units are connected through one phenyl substituent on each is reported. In three of the dimers, the subunits are linked directly, and in three others, they are linked via an alkane chain. A seventh new compound in which two 1,3-diphenylisobenzofuran units share a phenyl substituent is also described. These materials are needed for investigations of the singlet fission process, which promises to increase the efficiency of solar cells. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…Substantial efforts have been made to develop molecular systems suitable for efficient SF, and the number of chromophores that fulfill the necessary requirements, although somewhat limited, is currently increasing to include acenes,1722 diphenylisobenzofurans,2325 carotenoids,26,27 rylenes,2830 and others 3133. With a wider selection of potential SF-chromophores available, the more difficult task of deciphering the mechanistic and morphological details associated with SF must now be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Substantial efforts have been made to develop molecular systems suitable for efficient SF, and the number of chromophores that fulfill the necessary requirements, although somewhat limited, is currently increasing to include acenes,1722 diphenylisobenzofurans,2325 carotenoids,26,27 rylenes,2830 and others 3133. With a wider selection of potential SF-chromophores available, the more difficult task of deciphering the mechanistic and morphological details associated with SF must now be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…However, covalently linked SF dimers (Figure 1a) offer significant advantages for detailed mechanistic studies of SF due to their chemical tunability. [21][22][23][24][25][26] Recently, several reports have shown efficient intramolecular SF in isolated acene dimers and demonstrated that modifying their structure can systematically tune the rate of triplet pair generation and decay. [27][28][29][30][31] For example, we have previously employed acene heterodimers, systematically varying the energy of the (TT) states produced by SF, and uncovered an energy gap law which governs non-radiative triplet pair recombination.…”
mentioning
confidence: 99%
“…SF was first observed in crystalline anthracene, and has been extensively studied in this molecular system . SF has since been reported with high yields in polyacenes, such as tetracene, pentacene and their derivatives, oligophenyls, diphenylisobenzofuran, carotenoids, rylene‐based chromophores, perylenediimides, diketopyrrolopyrroles (DPP) derivatives, and some conjugated polymers . Efficient SF has been reported mainly in condensed matter systems, e.g., crystals, polycrystalline films, amorphous films, nanoparticles and aggregates .…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] Recent studies show that the correlated triplet pair ( 1 TT) state may convert first to a spatially separated triplet pair intermediate 1 (T…T) before it undergoes dephasing or decorrelation into two independent triplets. [2] SF has since been reported with high yields in polyacenes, [7,8] such as tetracene, pentacene and their derivatives, oligophenyls, [9] diphenylisobenzofuran, [10] carotenoids, [11,12] rylene-based chromophores, [13] perylenediimides, [14] diketopyrrolopyrroles (DPP) derivatives, and some conjugated polymers. [6] For SF the energy of the singlet state (E(S 1 )) should be greater than or equal to twice the energy of the triplet state (E(T 1 )), i.e., E(S 1 ) ≥ 2E(T 1 ).…”
mentioning
confidence: 99%